PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 025 SUNGAI TUNGGAK KECAMATAN KUBU - Supiah, Intan Supiah Intan; ', Zulkifli Zulkifli; ', Lazim N Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : This study departed from the low learning outcomes IPS ElementarySchool fourth grade students Tunggak 025 River Kubu district of Rokan Hilir. Theproblem of this study is: Does the application of learning by using the approachof Contextual Teaching Learning (CTL) can improve the learning outcomes of thefourth grade students of SD Negeri 025 Tunggak River in the Academic Year2013/2014 ?. The purpose of this research is to improve the social studies hasiElementary School fourth grade students Tunggak River 025. From the analysis ofthe data obtained were analyzed in implementing the learning activities ofteachers increased from 78.57% to both categories in the first cycle to 91.07%with both categories once in the second cycle. Student learning in a learningactivity increased from 65% with both categories in the first cycle to 90% withboth categories once in the second cycle. While the study results seen from theaverage score value and completeness of student learning, both individually andclassically increased in the first cycle of 15 students (75%) completed and thestudent does not complete 5 students (25%). While on the second cycle there are18 students who completed the students (90%) and students who did not complete2 students (10%). Average scores of students in the first cycle was 73.75, while inthe second cycle is 80.5. Although it is not said to be 100% complete, but showsan increase in each cycle.Keywords: Contextual teaching and learning, IPS Learning Outcomes